Elucidating the role of (p)ppGpp in mycobacterial persistence against antibiotics. Issue 9 (9th August 2018) - Bhaskar, Ashima; De Piano, Cyntia; Gelman, Ekaterina; McKinney, John D.; Dhar, Neeraj
Abstract: Bacterial persistence, the ability of bacteria to survive high concentrations of antibiotics for extended periods of time, is an important contributing factor to therapy failure and development of chronic and recurrent infections. Several recent studies have suggested that this persistence is mediated primarily by (p)ppGpp, through its interactions with toxin–antitoxin modules and polyphosphates. In this study, we address whether these key players play a role in mycobacterial persistence against antibiotics. We targeted these specific pathways in Mycobacterium smegmatis by constructing deletion strains of (p)ppGpp synthetase/hydrolase ( relA ), polyphosphate kinases ( ppk1 and ppk2 ), exopolyphosphatases ( ppx1 and ppx2 ), and the lon protease. None of these mutant strains exhibited altered levels of persisters against isoniazid and ciprofloxacin, when compared with wild‐type strain. Even under conditions in which the stringent response usually gets activated, these strains displayed wild‐type persister levels. Interestingly, we also found that unlike Escherichia coli, maintaining M. smegmatis in exponential phase by repeated passaging does not eliminate persisters suggesting that at least against the antibiotics tested, stationary‐phase dependent persisters (type I) are not the major contributors. Thus, our data demonstrate that multiple mechanisms of antibiotic persistence exist and that these vary widely among different bacterial species. © 2018 IUBMB Life, 70(9):836–844, 2018